Innovation and stock markets: international evidence on manufacturing and services. - Wójcik, D (School of Geography and Environment (University of Oxford), 2008)
The paper investigates the link between stock markets and innovation, by focusing on the relationship between firms' innovativeness and their participation in public stock markets. It reviews theoretical and empirical literature on capital structure and going-public decision, combined with insights from innovation studies, to argue that there are no reasons, why a positive relationship between innovativeness and stock market participation should not apply to both manufacturing and services firms. This hypothesis is confirmed through the analysis of data from 30 European countries, as well as the USA and Japan, which shows that the positive relationship between innovativeness and stock market participation is actually stronger for services than for manufacturing firms. It is also shown that the relationship differs between countries as a reflection of their diverse institutions. It is weak or absent in countries where institutional environment of stock markets is weak, e.g. transition economies or Italy, and pronounced where institutions are particularly stock market friendly e.g. the USA and the UK. Finally, the paper shows that while the Internet boom brought hoards of innovative firms to stock markets, the positive relationship between innovativeness and stock market participation is likely to have existed before. Implications are drawn for research on the impact of financial structure on innovation and growth.